2014
DOI: 10.1111/str.12088
|View full text |Cite
|
Sign up to set email alerts
|

Finite Element Analysis of the Microstructure of AlN–TiN Composites

Abstract: Finite element modelling (FEM) is performed on AlN-TiN composites. The structure-property relationships are studied for 5 and 10 vol.% TiN composites in view of thermal and thermo-mechanical properties. Thermal stresses are simulated at various temperatures for the 5 and 10% TiN samples in homogeneous and heterogeneous temperature environments. It is found that compressive stresses are associated with the microstructure and these stresses are largest at the interface of the AlN-TiN phases. In addition, thermal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…Similar kinds of pixel selection and properties assignment are used by many researchers where two-phase materials or composites such as Ni-Al [37], Al-MgO [19], WC-Al 2 O 3 [20] and AlN-TiN [21] for various applications. Moreover, a varying ZnO composition from 4-10% is also studied by Manish et al [2] for NBT-6BT-ZnO composites.…”
Section: Microstructure Image and Mappingmentioning
confidence: 99%
See 3 more Smart Citations
“…Similar kinds of pixel selection and properties assignment are used by many researchers where two-phase materials or composites such as Ni-Al [37], Al-MgO [19], WC-Al 2 O 3 [20] and AlN-TiN [21] for various applications. Moreover, a varying ZnO composition from 4-10% is also studied by Manish et al [2] for NBT-6BT-ZnO composites.…”
Section: Microstructure Image and Mappingmentioning
confidence: 99%
“…In the case of triangular element Ё S is defined as [13]: [2] Copyright © 2014 Wiley Publishing Ltd) (c) energy functional approach used during skeleton mesh refinement process [38], (d) final mesh with boundary conditions of NBT-6BT-4% ZnO (Reprint with permission from Ref. [21] Copyright© 2020 Elsevier BV).…”
Section: Skeleton Modification and Refinementmentioning
confidence: 99%
See 2 more Smart Citations
“…Sharma et al 17 examined thermal conductivity, thermal expansion coefficient, and modulus of elasticity for the interpenetrating phase composites of Ni/Al 2 O 3 using OOFEM. Patel et al 18 used OOF2 to study the structure–property relationships of AlN–TiN composites. It is found that compressive stresses are associated with the microstructure, and these stresses are largest at the interface of the AlN–TiN phases.…”
Section: Introductionmentioning
confidence: 99%